Articular and other Immune-Mediated Extra-Intestinal Manifestations in Inflammatory Bowel Diseases. (May 2014) - Peluso, R.; Iervolino, S.; Vitiello, M.; Bruner, V.; Ambrosino, P.; Manguso, F.; Castiglione, F.; Di Minno, M.N.D.
The articular involvement in patients with inflammatory bowel diseases is included in the group of immune-mediated extra-intestinal manifestations, occurring approximately in a range from 6.2–36% of the patients. This group is also made up of the skin and eyes manifestations, that usually but not invariably are correlated with intestinal inflammatory disease activity. Rheumatic manifestations are the most frequent extra-intestinal findings of this group with a prevalence from 20–50%. They are divided into two different clinical subsets: peripheral and axial joint involvement (including sacroiliitis with or without spondylitis). Peripheral arthritis is the most frequent finding in both Crohn's disease and ulcerative colitis, occurring with a frequency ranging from 17–20%, and it is more common in Crohn's disease. Axial involvement is more common in Crohn's disease (5–22%) than in ulcerative colitis (2–6%) and generally the prevalence of sacroiliitis (asymptomatic and symptomatic) is between 12–20% and of spondylitis is between 2–16%. The IBD is also associated with other rheumatic diseases such as rheumatoid arthritis, Sjogren syndrome, Takayasu arteritis and fibromyalgia. The management of patients with EA requires an active cooperation between gastroenterologists and rheumatologists.